(untitled) (Revista de História Regional, 2007)
The article intends to analyse the patriot discourses based on the concepts of governability in Foucault and myth in Roland Barthes built up about the city of Curitiba in the 19th century and in the begining of the 20th century by european travelers and chroniclers. These discourses are analysed like important elements on the build on the pacific, disciplined and laborious town, trought capitalist trade relations. It is where the continuous action of the town towards progress and development takes place.